Bioactive compounds: A contribution to the teaching of Organic Functions in the Chemistry Degree course (Research, Society and Development, 2021)
In the teaching of chemistry, it is noticed that students are often unable to learn, are not able to associate the content studied with their daily lives, becoming disinterested in the topic. Thus, there is a need to contextualize the content addressed in the classroom with the student's daily life, thus facilitating learning. The theme organic functions is a subject of fundamental importance in Chemistry, in which students still find difficulties, due to the memorization of concepts and classifications. With this in mind, the present work aims to present an analysis of the results obtained from the contextualized approach to the study of organic functions present in bioactive compounds existing in natural compounds. Expository / interactive class, discussions and questionnaires were applied, in order to analyze the students' knowledge about the theme and facilitate the learning process. The identification of organic functions approached in a contextualized way provided students with a view on how the chemistry of natural products is present in our daily lives and, thus, facilitated the learning of the content on organic functions, showing the influence of contextualization in the teaching of chemistry improving learning.